The Internet Of Things Technology Acceptance In Supply Chain Management - Kanagesvari, Arjeenan (2024)
This study explores into the Internet of Things (IoT) technology acceptance in Supply Chain Management (SCM) in Malaysia. The advent of Industry 4.0 has ushered in modern information technologies that not only enhance supply chain effectiveness but also redefine organisational operations. As a result, cutting-edge technology like the IoT is projected to have a significant impact on business operations and supply chain management SCM. In addressing the challenges faced by traditional SCM, the research underscores the significance of IoT acceptance in mitigating risks and improving overall efficiency in SCM. This study investigates on the relationship between real-time visibility, data-driven decision-making, perceived usefulness, and perceived ease of use with the IoT technology acceptance in SCM. The study also applied the Technology Acceptance Model (TAM) framework, to provide a holistic understanding of the level of acceptance of IoT. The questionnaire was used as the instrument in collecting data from the respondents. There were 400 questionnaires distributed randomly to the respondents and 361 were returned to the researcher. Pearson Correlation Analysis was used to assess the strength of the correlations between the variables and to determine how strongly two variables are related to each other. Findings have shown that there was a significant relationship between real-time visibility with IoT technology acceptance in SCM (r = 0.915), data-driven decisionmaking with IoT technology acceptance in SCM (r = 0.899), perceived usefulness with IoT technology acceptance in SCM (r = 0.762) and perceived ease of use with IoT technology acceptance in SCM (r = 0.394). Based on the results of the research, the results showed that all the factors studied had positive relationship with the IoT technology acceptance in SCM. In conclusion, this study emphasises the significance of IoT technology within SCM and provides valuable insights and contributions to facilitate its broad adoption and practical application among employees. This study can be a guideline to every organisation in decision to accept IoT technology. The limitations and recommendation for future study has been highlighted in this study.